2004
DOI: 10.2337/diacare.27.6.1517
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Motivation and Glycemic Control in Adolescents with Type 1 Diabetes

Abstract: Diabetic patients have been shown to excrete increased quantities of albumin, which is undetectable by conventional albumin antibodies (immunounreactive) using high-performance liquid chromatography (HPLC) (1). Furthermore, the lead time for the development of microalbuminuria (albumin excretion rate [AER] Ͼ20 g/min) measured by HPLC has been shown to occur 3.9 and 2.4 years earlier than that determined by radioimmunoassay (RIA) for type 1 and type 2 diabetic patients, respectively (2). This study not only ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…A previous study, demonstrated that individuals who persisted in a specific educational course were more intrinsically and less extrinsically motivated, and that intrinsic motivation augmented self‐efficacy towards physical activity . Adolescents who are intrinsically motivated to manage their health are more likely to report adhering to their treatment . In addition, patients with intrinsic motivation have significantly better adherence to long‐term medication …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A previous study, demonstrated that individuals who persisted in a specific educational course were more intrinsically and less extrinsically motivated, and that intrinsic motivation augmented self‐efficacy towards physical activity . Adolescents who are intrinsically motivated to manage their health are more likely to report adhering to their treatment . In addition, patients with intrinsic motivation have significantly better adherence to long‐term medication …”
Section: Discussionmentioning
confidence: 97%
“…39 Adolescents who are intrinsically motivated to manage their health are more likely to report adhering to their treatment. 17 In addition, patients with intrinsic motivation have significantly better adherence to long-term medication. 18 A randomized control trial showed that an intervention that promotes an intrinsic motivation towards physical activity was associated with significant weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Greening et al (2004), intrinsic motivation was found to be positively associated with adherence to treatment regimens among adolescent study participants living with Type-l diabetes.…”
Section: Autonomous Regulation and Self-managementmentioning
confidence: 98%